P2Y12 Receptors Play a Significant Role in the Development of Platelet Microaggregation in Patients with Diabetes - Matsuno, Hiroyuki; Tokuda, Haruhiko; Ishisaki, Akira; Zhou, Yuan; Kitajima, Yasuo; Kozawa, Osamu (The journal of clinical endocrinology and metabolism, 2005)
Ninety-eight diabetic patients (type 2) were studied together with 24 healthy normotensive controls. Microaggregates (particle scale, <25 μm) of platelets were detected by a laser scattering system. Microaggregates in the control group showed a time-dependent reversible change; however, they existed continuously in 82 of 98 diabetic patients. When platelets of diabetics were stimulated by a shear stress alone without ADP, 74 also showed spontaneous and irreversible microaggregates even though they were not observed in all control subjects. In control subjects, microaggregates were inhibited by MRS2279 (a P2Y1 antagonist), but not AR-C69931MX (a P2Y12 antagonist). However, AR-C69931MX prevented irreversible microaggregates in diabetic patients. When either aspirin or ticlopidine was administered to diabetic patients with irreversible microaggregates, both drugs significantly decreased microaggregates induced by a low dose of ADP. Ticlopidine additionally reduced the microaggregates induced by shear stress alone. In conclusion, microaggregates of platelets via P2Y12 receptors could play a key role in the hypersensitivity of platelets in diabetic patients, and the measurement of microaggregation could be a useful marker to estimate of thrombogenesis. These findings present a possible new means for patients with diabetes to prevent ischemic events.